Cerebral blood flow during treatment for pulmonary hypertension. Issue 1 (1st January 1999) - Kusuda, Satoshi; Shishida, Norio; Miyagi, Nobuhiro; Hirabayashi, Madoka; Kim, Tae-Jang
Abstract : AIM: To determine if the haemodynamics of systemic and cerebral circulation are changed during treatment for persistent pulmonary hypertension of the newborn (PPHN). METHODS: Fifteen term newborn piglets with hypoxia induced pulmonary hypertension were randomly assigned either tolazoline infusion (Tz), hyperventilation alkalosis (HAT), and inhaled nitric oxide (iNO). Mean pulmonary arterial pressure (PAP), mean systemic arterial pressure (SAP), and cerebral blood flow volume (CBF) were measured. RESULTS: During hypoxic breathing, PAP increased significantly in all groups. After treatment PAP decreased significantly in all groups, but no significant difference was observed between groups. SAP decreased significantly only in the Tz group, and CBF reduced significantly only in the HAT group. On the other hand, iNO did not change SAP or CBF. CONCLUSION: Inhaled NO might be ideal for the resolution of pulmonary hypertension.